La percepción de las estructuras formales de las peticiones en L2 - Jódar, Raúl Fernández (Studia Romanica Posnaniensia, 2023)
There are different formal structures which requests can be made with depending on the register used and the degree of courtesy. During the teaching process, these structures are introduced according to their recursiveness and difficulty, and not necessarily due to their courtesy. This can cause mismatches between the perception of requests in L2 and in L1. In this paper we intend to analyze if this is really the case, or if there are no differences in the perception of these structures in L1 and L2.